Muscle Fiber and Meat Quality Characteristics of longissimus dorsi and biceps femoris in Sunit Sheep - LI Jin, HE Baolong, HE Xige, HAN Yunfei, CHEN Lu, HUANG Yajuan, BORJIGIN Gerelt (Shipin Kexue)
This study was carried out in order to explore the differences in muscle fiber and meat quality characteristics between the longissimus dorsi (LD) and biceps femoris (BF) msucles of Sunit sheep. The muscle fiber characteristics were determined by ATPase histochemical staining and real-time fluorescence quantitative polymerase chain reaction (real-time PCR), and the eating quality (pH, color, cooking loss rate, and hardness) was evaluated. Additionally, the correlations of the muscle fiber characteristics and MyHCs gene expression with the eating quality were analyzed. The differences in nutrient composition (moisture, protein, intramuscular fat, ash, amino acids, and fatty acids) and flavor substance contents were also compared between the two muscles. The results showed that the proportion of type IIB fibers was significantly higher in LD than in BF (67.90% versus 53.69%, P < 0.05), while the proportion of type I fibers was significantly lower in LD (P < 0.05). Lower average diameter and higher density of muscle fibers were observed in LD. The expression of the MyHC I and MyHC IIA genes were significantly lower in LD than in BF, and the expression of the MyHC IIB gene was significantly higher in LD (P < 0.05). The pH45 min and lightness values of LD were significantly higher than those of BF, while the pH24 h, redness values, cooking loss rate, and hardness were significantly lower those of LD (P < 0.05). There was a significantly positive correlation between the brightness value and the proportion of type IIB fibers, as well as between the redness value and the proportion of type I fibers (P < 0.05). LD had significantly higher moisture content but significantly lower intramuscular fat content than did BF (P < 0.05). The contents of threonine, aspartic acid, serine, glutamic acid, proline, glycine, and alanine were significantly lower in LD than in BF (P < 0.05). The contents of arachidonic acid and docosahexaenoic acid were significantly higher in LD than in BF (P < 0.05). The contents of hexanal and 1-heptanol were significantly lower in LD than in BF, while the contents of butyric acid and 4-nonanone were significantly higher in LD (P < 0.05). This study provides a theoretical basis for grading, primary cutting, and deep processing of Sunit lamb.